The Battle Over Hasidic Radicalism: The Belz-Munkács Controversy - Gelman, Uriʾel (Jewish studies quarterly, 2023)
Throughout its history Hasidism has faced various challenges, including frequent internal controversies that augmented its ramified social and cultural frameworks. Many of these controversies have revolved around competition and political antagonism rather than ideological or theological incentives. This article addresses a harsh controversy that erupted between the Belz and Munkács Hasidic groups after the First World War. This feud reflects the profound challenges that Jewish lay leaders and rabbis faced during this period, clarifies the socio-political considerations of the Hasidic rebbes, and affords readers a better understanding of the idiosyncratic anatomy of intra-Hasidic controversies. The reconstruction of the drama of the Belz-Munkács controversy, which has thus far attracted no scholarly attention, reveals an important and unfamiliar chapter in the evolution of interwar Jewish fundamentalism.